The role of production factors on landings heterogeneity between EU countries. (October 2021) - Inguanzo, Belén; Gutiérrez, María-José; Orbe, Susan
Abstract: Distribution of natural resources is considered to be a key aspect in ensuring the success of conservation policies. The Common Fisheries Policy, implemented by the European Union (EU), is an example of long-term international cooperation for sustainability of the marine environment. Nonetheless, continued enforcement of the policy is threatened by its insufficient effectiveness in restoring fish stocks and the tensions that have arisen over unequal distribution of benefits. Recent adoption of the Blue Growth Strategy represents an additional challenge for EU fisheries, since it encourages new alternative economic activities. The present analysis aims to identify ways of enhancing the sustainability of EU fisheries while achieving greater equity in resource distribution and maintaining the activity of the fishing industry, an important staple of many coastal communities in the EU. To this end, the study decomposes heterogeneity amongst per capita landing rates of EU Member States. A number of findings from the decompositions used may be highlighted. Firstly, most of the heterogeneity in per-capita landing rates between Member States occurs within the main EU fishing areas, especially FAO Areas 27 and 37. Secondly, fishing production factors affect per-capita landing heterogeneity to a different extent in Areas 27 and 37. The only exception is the number of fishers, the factor contributing most to heterogeneity in both areas. Technological factors appear to diminish heterogeneity in Area 27 whilst positively contributing to heterogeneity in Area 37. More efficient fleet adjustments could be designed taking into account these contributions by production factors to heterogeneity within fisheries. Highlights: The distribution of EU fishery resources is more unequal within fishing areas. The number of fishers contributes the most to heterogeneity within EU fisheries. Technological factors reduce landings heterogeneity in FAO Area 27. Technological factors increase landings heterogeneity in FAO Area 37.